Narcolepsy: a clinical review. Issue 5 (15th May 2014) - Leschziner, Guy
Abstract : Despite the classic tetrad of clinical features that typify it, narcolepsy remains much under-diagnosed, in part, because of the wide spectrum of clinical phenotypes, but also because of its insidious onset, usually in a young person. The median time to diagnosis from first symptoms remains very long, around 10 years in the UK. Conversely, in the specialist setting, it is likely over-diagnosed, largely because of failure to exclude other causes of hypersomnia. There is an over-reliance on a biological marker of the condition, the multiple sleep latency test (MSLT), which, like many tests, has a significant false-positive and false-negative rate. This review aims to discuss some of the difficulties in achieving a diagnosis, interpretation of investigations, differential diagnosis, and appropriate management of patients with narcolepsy.